Pengolahan Kopi Bubuk dan Pemasaran Berbasis Digital Marketing dalam Meningkatkan Daya Saing Hilirisasi Kopi di Kawasan Lereng Menoreh - Ahmad, Masrukan; Perdana, Fahmi Rafika; Utami, Kristiana Sri; Harjanta, Sri Lestari (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2019)
Diversification of post-havesting of coffe managed by the coffee farming group in the Sidoharjo district, Kulonprogo has several problems in post-harvest handling and processing coffee, especially in processing of coffee powder Â with good manufacturing process (gmp) as well as conventional marketing management. Through the Community Partnership Program (PKM), the service team provide solutions to outcome problems through several methods; 1) training and assistance in post-harvest handling Â 2) training and assistance in the production of ground coffee in a natural process and 3) training and assistance in marketing management with digital marketing. The results of the assistance are the post-harvest handling and processing of coffee properly and correctly by producing ground coffee with the brand name "Lemon" as well as better managed marketing, not only in a conventional manner but also by using marketing based technologoy (www .kopilemon.com). With this Community Partnership Program, it has an impact on increasing the competitiveness and welfare of coffee farmers in the Menoreh area